Discrete dipole approximation for calculating optical properties of ZnO nanoparticles and ZnO-PVP composites. Issue 12 (15th August 2018) - Patra, Subhasish; Sengupta, Payal; Ray, Apurba; Roy, Atanu; Das, Sachindranath
Abstract: Discrete dipole approximation (DDA) is a well-known method which is generally used to simulate the interaction of nanoparticles with the electric field of incident light. In this paper, DDA has been used to simulate different optical properties (absorption efficiency factor, scattering efficiency factor, extinction efficiency factor, phase lag efficiency factor and 3D near electric field) of ZnO nanoparticles (NPs) and ZnO-PVP composite. The particle sizes are varied and size corrected complex dielectric function of ZnO and its composite have been used as inputs of the simulation. The particle sizes of ZnO NPs and ZnO-PVP composites have been varied from 22 nm to 38 nm in simulation. The peak position of absorption efficiency factor matches perfectly with the experimental absorbance when the size of ZnO NPs is taken as 26 nm. The same phenomenon happens in case of ZnO-PVP composite when the size of composite NPs is considered as 28 nm. The particle within dielectric medium acts as particle with higher effective radius as the near electric field increases due to presence of local dielectric medium. We have also calculated other optical parameters of ZnO NPs and ZnO-PVP composites. Small but not negligible changes in optical properties are observed due to incorporation of PVP with ZnO nanoparticles.